2013
DOI: 10.1039/c3cp44627a
|View full text |Cite
|
Sign up to set email alerts
|

On the dual emission of p-dimethylaminobenzonitrile and its photophysical implications

Abstract: A solvatochromic analysis of available absorption and LE and TICT emission data in p-dimethylaminobenzonitrile (DMABN) was conducted. Applying the Abe method to the results of a thermochromic analysis of DMABN in 1-chlorobutane (ClB) allowed us to determine the polarizability and dipole moment of the excited electronic states involved in the absorption and emission transitions. As shown herein, the LE → TICT excited state reaction for DMABN is triggered by the solvent polarity but is additionally influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 68 publications
2
41
1
Order By: Relevance
“…This corresponds to processes that undergo photodissociation leading to the loss of hydrogen. 30 The other depicts processes in which the s* orbital is placed in a triple bond and thus promotes the rehybridisation from sp to sp 2 , as is the case in the present study. For the case of DMABN and some related molecules, the evidence of the participation of ps* states in the relaxation processes leading to the population of ICT states rests upon recent experimental studies carried out by Lim, Gustavsson and co-workers.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…This corresponds to processes that undergo photodissociation leading to the loss of hydrogen. 30 The other depicts processes in which the s* orbital is placed in a triple bond and thus promotes the rehybridisation from sp to sp 2 , as is the case in the present study. For the case of DMABN and some related molecules, the evidence of the participation of ps* states in the relaxation processes leading to the population of ICT states rests upon recent experimental studies carried out by Lim, Gustavsson and co-workers.…”
Section: Introductionsupporting
confidence: 56%
“…This model was soon challenged and since then, a long-standing effort has been carried out with the aim of understanding the molecular basis of this phenomenon. However, despite the large number of studies reported to date on this topic, the molecular mechanism underlying the dual fluorescence is still the focus of heated controversy, [2][3][4] in part due to the complexity of the process that involves multiple electronic states and where solvent effects are all important, which makes its characterisation especially challenging from both theoretical [5][6][7][8] and experimental [9][10][11][12] standpoints.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Though several mechanisms were propsed to demonstate formation of the ICT state, the twisted ICT (TICT) model proposed by Grabowski et al is widely accepted. [4][5][6][7][8][9][10][11][12] A close look reveals that other than polarity and viscosity, the hydrogen bonding also strongly influence the TICT process of numerous systems. 4,5 In other words, that the donor is perpendicular to other part of the molecule in the ICT state.…”
Section: Introductionmentioning
confidence: 99%
“…More than 1000 research papers and numerous extensive reviews have been devoted to this phenomenal chromophore. [2][3][4][5][12][13][14][15] Interestingly, excimer emission, which is a competing process for numerous other aromatic chromophores such as anthracene and pyrenes, [16] has not been characterized for DMABN in the solution phase. [2][3][4][5][6][7][8] The fundamental issues associated with the dual fluorescence of DMABN relate to the reaction pathway that connects the two states [1,2,4,7,[9][10][11][12] and the geometrical structure of the emitting ICT state.…”
Section: Introductionmentioning
confidence: 99%
“…Only a single report, relating to the gas phase, pointed to an intermediary emission band at around 400 nm, which was tentatively ascribed to a DMABN cluster. Interestingly, in early studies, [5,32,33] the long-wavelength emission of DMABN itself was incorrectly assigned as the excimer emission, whereas in later studies, after the longwavelength emission had been identified as being due to ICT, the excimer has been repeatedly invoked as a dark state. [23][24][25][26] They form inclusion complexes by encapsulating hydrophobic residues of small organic guests in their inner cavity, while their carbonylrimmed portals can stabilize positive charges of the guest molecule, if present.…”
Section: Introductionmentioning
confidence: 99%